Observing international relations : Niklas Luhmann and world politics - Albert, Mathias; Hilkermeier, Lena, 1971- (New international relations., 2004)
Observing International Relations draws upon the modern systems theory of society, as developed by Niklas Luhmann, to provide new perspectives on central aspects of contemporary world society.